The Role of Social Capital on Community Resilience in Rural Areas: A Case Study in Ponggok Village, Indonesia - Nugraha, Achmad Tjachja; Fikriyah; Zahara, Sylvia; Suhartini, Wildan; Zahid, Umair; Hlahla, Jeremiah (Journal of Regional and Rural Studies, 2024)
Natural disasters have an impact on the socio-economics of society. Therefore, community resilience in facing these disasters is essential. Social capital is one factor that can help strengthen community resilience. This research will take an approach from social capital that consists of trust, social networks, and norms with collective action and community resilience. So, the research objective is to determine community resilience through collective action at the post-disaster recovery stage. Research was conducted in Ponggok Village to answer these research questions, which has abundant water resources as the village's superior potential. The Krejcie and Morgan tables determined the sample and showed the results in 248 respondents' families. The analysis used is Descriptive Statistics and Partial Least Square (PLS)-Structural Equation Modeling (SEM). Through the analysis accomplished, the study shows that social capital significantly impacts 99% of the collective actions of society and government in dealing with disasters. Community resilience and social capital had an R2 of 0.316 (31.6%), a moderate explanation of the variance.  However, this research still acquires confines despite the significant results. Therefore, the role of the community and government is crucial in achieving better resilience.